Morbidity and mortality related to odontoid fracture surgery in the elderly population - White, Andrew P; Hashimoto, Robin; Norvell, Daniel C; Vaccaro, Alexander R (Spine (Philadelphia, Pa. 1976), 2010)
Systematic analysis. To determine the morbidity and mortality of surgical treatment of odontoid fractures in the elderly. The prevalence of trauma in the elderly is increasing. There exists no consensus regarding the role of surgical treatment for odontoid fractures in the elderly and there exists significant variability in clinical practice. This variability may be related to a lack of robust information available to clinicians. Importantly, studies that define surgical risk are not available. A systematic analysis of the English language literature was undertaken for articles published between January 1990 and June 2009. Electronic databases and reference lists of key articles were searched to identify articles examining complications and mortality following odontoid fracture surgery in subjects 65 years of age or older. Two independent reviewers assessed the level of evidence quality using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) criteria, and disagreements were resolved by consensus. The initial literature search yielded 247 articles related to morbidity or mortality following surgery treatment of odontoid fractures in the elderly. After exclusion of articles based on title or abstract information, 48 remained to undergo full text review. Subsequent exclusions yielded 14 articles suited for this analysis. The most commonly reported major complications after odontoid fracture surgery in the elderly include cardiac failure (6.8%), DVT (3.2%), stroke (3.2%), pneumonia (9.9%), respiratory failure (7.7%), liver failure (6.7%), and severe infection (3.2%). Other site specific and minor complications were found to be reported consistently in the literature. The overall mortality rate after surgery is 10.1% (in-hospital, 6.2%; postdischarge, 8.8%). Similar mortality rates were found following anterior surgery (7% in-hospital; 9% overall) and posterior surgery (8% in-hospital; 9% overall); there were no differences in the rate of major airway complications between these groups (anterior: 17%; posterior: 18%). There was, however, a higher rate of site-specific complications, including nonunion, technical failure, and the need for revision surgery, following anterior surgery as compared with posterior surgery. Based on the summary of criteria results, future research evaluating complications following surgery for odontoid fractures in elderly patients is very likely to have an important impact on our confidence in the estimate of effect and is likely to change the estimate currently available in the literature.